1978
DOI: 10.1073/pnas.75.2.989
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and guanylate cyclase activity of an undifferentiated prostate adenocarcinoma by an extract of the balsam pear (Momordica charantia abbreviata).

Abstract: We have recently described the presence of a guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.21 inhibitor (GCI) in an aqueous extract of the balsam pear (Momordica charantia abbreviata). Because the guanylate cyclase-cyclic GMP system is thought to be involved in cell growth, DNA and RNA synthesis, and possibly malignant transformation, we examined the effect of the aqueous extract containing GCI on an undifferentiated adenocarcinoma of the rat prostate and concanavalin-A-stimulated [3Hlthymid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 24 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Detailed studies showed that MC acted through inhibition of cell cycle G2 and M phases (Claflin et al, 1978) through inhibition of incorporation of thymidine, leucine and uridine into DNA (Claflin et al, 1978;Chan et al, 1992;Ng et al, 1994). In addition, inhibition of guanylate cyclase activity (Vesely et al, 1977;Claflin et al, 1978;Takemoto et al, 1980Takemoto et al, , 1982b, activation of NK cells (Jilka et al, 1983;Cunnick et al, 1990;Porro et al, 1993), induction of apoptosis Sun et al, 2001) and modulation of biotransformation and detoxification enzymes of the host were also seen with MC (Kusamran et al, 1998;Singh et al, 1998;Ganguly et al, 2000).…”
Section: Mechanism For Anticancer Activitymentioning
confidence: 91%
See 3 more Smart Citations
“…Detailed studies showed that MC acted through inhibition of cell cycle G2 and M phases (Claflin et al, 1978) through inhibition of incorporation of thymidine, leucine and uridine into DNA (Claflin et al, 1978;Chan et al, 1992;Ng et al, 1994). In addition, inhibition of guanylate cyclase activity (Vesely et al, 1977;Claflin et al, 1978;Takemoto et al, 1980Takemoto et al, , 1982b, activation of NK cells (Jilka et al, 1983;Cunnick et al, 1990;Porro et al, 1993), induction of apoptosis Sun et al, 2001) and modulation of biotransformation and detoxification enzymes of the host were also seen with MC (Kusamran et al, 1998;Singh et al, 1998;Ganguly et al, 2000).…”
Section: Mechanism For Anticancer Activitymentioning
confidence: 91%
“…In addition, inhibition of guanylate cyclase activity (Vesely et al, 1977;Claflin et al, 1978;Takemoto et al, 1980Takemoto et al, , 1982b, activation of NK cells (Jilka et al, 1983;Cunnick et al, 1990;Porro et al, 1993), induction of apoptosis Sun et al, 2001) and modulation of biotransformation and detoxification enzymes of the host were also seen with MC (Kusamran et al, 1998;Singh et al, 1998;Ganguly et al, 2000). Lee et al (1998) demonstrated inhibition of tumor-promoting signals from the extracellular environment to nuclear transcription machinery as well as protein-DNA interaction with momordin treatment.…”
Section: Mechanism For Anticancer Activitymentioning
confidence: 92%
See 2 more Smart Citations
“…An extract from the bitter melon ripe fruit and leaves is reported to inhibit guanylate cyclase activity specifically and to block acti vation by nitroso chemical carcinogens [4,5]. We have found that this extract also inhibits guanylate cyclase from human lymphocytes, is specifically cytotoxic to leukemic human lymphocytes, and lowers cellular cyclic GMP Guanylate cyclase, the enzyme that cata lyzes the formation of cyclic GMP from GTP, exists in both soluble and particulate fractions of most tissues [1][2][3].…”
Section: Introductionmentioning
confidence: 99%